DISKURSUS ETIKA BISNIS ISLAM DALAM DINAMIKA BISNIS KONTEMPORER - Ardi, Mulia (IAIN Tulungagung, 2015)
Islamic business ethics are universal ideas that are relevant to the business world. The value that is contained in the Islamic business ethics in line with the needs of the conventional business value. Various problems faced by the contemporary business is basically caused by the lack of understanding of human identity. This ignorance leads to negative behavior of businesses in running a business. The essence of business is essentially the fulfllment of human needs. Duties and responsibilities of Islamic business ethics is delivering business activities on the essence of business and self-awareness. However, the implementation of Islamic business ethics at the level applicable is not easy. Islamic business ethics brings challenges and dilemmas, especially when faced with the dynamics of contemporary business.Key Words: Ethic, Islamic Business Ethic dan Contemporary Business